Iniciativa cintur\~ao e rota na América Latina: Perspectiva geoeconômica - Carlos Renato da Fonseca Ungaretti Lopes Filho; Ticiana Gabrielle Amaral Nunes; Giulia Marianna Rodrigues Di Marco; Marco Aurélio Alves de Mendonça (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
– The article follows concepts from the field of International Political Economy (IPE). Its objective is to analyze the evolution of economic relations between China and countries in Latin America and the Caribbean (LAC), especially in the context of the Belt and Road Initiative (BRI), or New Silk Road. Economic interactions have increased in the last decade, especially through trade, investments, loans and infrastructure projects.
10419/284875
Keywords: F10; F30; F34; F50; F55; F59; F6; 330; China; Latin America and the Caribbean; Belt and Road Initiative; foreign direct investment; infrastructure